Principles behind Carbon Dating and its Various Uses - Patra, Prashant Kumar (SCHOOL SCIENCE, 2014)
Sometimes we are very curious to know the age of ancient objects whose origin and age cannot be determined exactly by normal means, for example, objects dug up by archaeologists. If the object contains radioactive element, an element capable of emitting radiations spontaneously in the form of alpha particle, beta particle or gamma ray, then it is possible to estimate its age using radiometric (also called radioactive) dating method. There are a number of radiometric dating methods such as radiocarbon dating, uranium-lead dating and potassium-argon dating, etc. Among them, carbon dating is the most well-known method used in dating of archaeological specimens. Carbon dating is applicable only to organic materials, that is, the material must once have been a part of living things such as bone, wood, etc. In this method, the age of ancient objects are estimated by measuring their content of carbon-14 (C-14), a radioactive form of carbon with a nucleus containing 6 protons and 8 neutrons, called radiocarbon. This method is known as carbon dating or radiocarbon dating. However, this method cannot be applied to date metal, stone and pottery unless there is some organic material left as a residue. For objects that were never living, other radiometric dating methods are used.